Study on Influencing Factors and Countermeasures of Elderly Nursing Services in the Elderly. (16th May 2022) - Liu, Shuo; Chen, Li; Li, Dandan; Yang, Qianqian; Liu, Fangfang; Cheng, Yanli
Abstract : Objective and Background . In order to explore the needs of the elderly for elderly nursing services, this paper studies from this aspect; China's economic development, scientific, and technological progress and concepts have also changed. Although the living conditions of the Chinese people have improved, the rapid growth of the population has led to an aging society. Therefore, great attention has been paid to the care of the elderly. In addition, with the fast pace of life, many elderly people with chronic diseases, poor physical conditions, and need spiritual comfort are in a state of lack of care for a long time. It has affected the stability and harmony of Chinese society. Methods . 500 inpatients with chronic diseases in a famous tertiary hospital in a city were studied, and the corresponding countermeasures were put forward through the analysis of their needs and influencing factors. Results. The study found that the vast majority of elderly patients have higher requirements for elderly care services, which is related to factors such as family income. Compared with the huge medical demand, there is a large gap in the level of domestic medical and health talents. According to relevant research, the current number of beds in China is 1 : 0.27, but in fact it is 1 : 0.4. Therefore, relevant units should strengthen the health examination of the elderly, provide high-quality medical services, make full use of health resources, and strengthen nursing management, so as to improve the quality of nursing services. Conclusion . The survey results show that the vast majority of elderly patients have high requirements for their elderly care services, which is related to family income and other related factors. Therefore, relevant departments should formulate corresponding measures to improve the quality of life of the elderly.